Rivalitas Strategi Maritim China dan India di Selat Malaka (Insignia: Journal of International Relations, 2014)
Regarding the significance of Malacca Strait as a key maritime’s “choke-point” passage betweenIndian and Pacific oceans, some major countries become dependence with the security and safetyin Malacca Sea Lines of Communications (SLOC). China and India are two states-user ofMalacca Strait which sharing common interests of economic, maritime trade and energy supplies.The problem is, as a regional power of each region, India and China have an ambition to controlthe security of Malacca’s Strait. China which is more dependent with its 80% trade and energysupply through Malacca Strait, facing “Malacca dilemma” regarding the issue. Then, with thestrategy of “string of pearls” and the modernization of of People’s Liberation Army Navy (PLAN),China became assertive to save its interests. India, which has control over Indian Ocean then feelthreaten by China’s activities around Malacca Strait and Indian Ocean. India starts and enhancesthe development of Andaman Nicobar Command with US support near Malacca Straits to counterChina’s development. This paper will analyze the development of China’s dan India’s maritimestrategy rivalry in Malacca Straits with the concepts of balance of power and maritime strategy. Keywords:  Malacca Strait, China’s maritime strategy, India’s maritime strategy, rivalry, balanceof power